2014
DOI: 10.1177/1099636214548614
|View full text |Cite
|
Sign up to set email alerts
|

Improved extended high order analysis of sandwich beams with a bilinear core shear behavior

Abstract: The response of a sandwich panel with bilinear constitutive behavior for shear stress of a core is presented based on a proposed improved extended high order sandwich panel theory. In this theory the face sheets are analyzed based on the first order shear deformation theory that is hitherto not applied in the conventional extended high order sandwich panel theory. Besides, the two-dimensional (2D) elasticity is used for the core. The field equations are derived using the Ritz-based solution which is suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…3 and 4 respectively. The value of the shear stress for various bilinear ratio are in good agreement with results off [20], but the trend of the shear stress is slightly different. This difference is due to the difference of the solution procedure.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…3 and 4 respectively. The value of the shear stress for various bilinear ratio are in good agreement with results off [20], but the trend of the shear stress is slightly different. This difference is due to the difference of the solution procedure.…”
Section: Resultssupporting
confidence: 80%
“…They employed the Ritz based solution procedure to extract the results. The geometrical and mechanical properties of the panel are presented in Table (1). The results of [20] and the results of present study are shown in Figs. 3 and 4 respectively.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Growing popularity of sandwich structures led to numerical implementation of shell theory formulations appropriate for these kinds of structures [29][30][31][32][33][34][35]. However, since the FEM model has to be able to predict localised failure modes, core was modelled with solid elements, based on similar research [5][6][7][8][9][10][11][22][23][24].…”
Section: Fem Model Descriptionmentioning
confidence: 99%